Aptamer-Based Lateral Flow Test Strip for the Simultaneous Detection of Salmonella typhimurium, Escherichia coli O157:H7 and Staphylococcus aureus. (3rd March 2020) - Lu, Chunxia; Gao, Xiaoxu; Chen, Ya; Ren, Jiangtao; Liu, Changbin
Abstract: An aptamer-based lateral flow test strip was developed for the simultaneous detection of Salmonella Typhimurium, Escherichia coli O157:H7, and Staphylococcus aureus . This assay was based on the sandwich-type format using primary aptamer conjugated with gold nanoparticles (AuNPs) as the signal probe and a secondary aptamer-coated membrane as a capture probe. Several experimental conditions that influenced sensitivity were investigated, including the aptamer and NaCl concentrations and the loaded amounts of gold nanoparticle–aptamer conjugates and streptavidin–aptamer conjugates. Under the optimal experimental conditions, the visual limits of detection of the strip for S. Typhimurium, E. coli O157:H7 and S. aureus were 10 3 CFU/mL, 10 4 CFU/mL, and 10 4 CFU/mL, respectively. All measurements were achieved within 10 min, and no significant cross-reactivity with several foodborne pathogens was observed. This aptamer-based strip was successfully applied to the simultaneous detection of these foodborne pathogens in food samples. The aptamer-based lateral flow test strip was shown to provide a reliable, simple and accurate tool for the simultaneous detection of multiple foodborne pathogens.